ANALISIS PERILAKU ALIRAN TERHADAP KINERJA RODA AIR ARUS BAWAH UNTUK PEMBANGKIT LISTRIK SKALA PIKOHIDRO - Jamlay, Kristianus; Sule, Luther; Hasan, Duma (Dinamika Teknik Mesin, 2016)
Energy of water is one of the renewable energy that can be converted into electrical energy without pollution. Rotation, torque, and power generated by the water wheel can be used directly both for irrigation pumping and for running a rice mill even move the alternator and electrical generators. The purpose of this study was to find the best water wheel performance indicated by torque, rotation, and power as well as the relative speed of the water at the side of the blade. The results obtained in the preliminary test were the average water velocity of 2.50 m/s, the average rotation shaft of 79.78 rpm, the average torque on the shaft of 58.98 Nm, the average power of 510,67 W. The second results were also obtained as given the results and discussion section. It was found that the best water wheel performance based on the analysis was shown in the second test results.